G297(P) Use of email advice – line to improve management of children in the community. (27th April 2015) - Montgomery-Taylor, S; Cotton, R; Manek, N; Watson, M; Klaber, R
Abstract : Aims: Our innovative integrated child – health programme puts the GP practice at its heart bringing specialist expertise and support into primary care. "Open access" is one key component and includes an email advice – line for community health – professionals to contact paediatricians for advice. Registrars wrote replies and the aim was to respond within 1 working day. The aim of this project was to evaluate the use and perceived effectiveness of the email advice line on management of children in the community. Methods: 451 emails sent by GPs and community health professionals over 10 months were reviewed. The final outcome of the email advice was categorised by three reviewers independently, with a paediatric consultant providing input when a consensus was not reached. Forty randomly selected community professionals and six paediatric registrars were contacted to provide feedback. Results: 99.6% of responses came from 91 GP practices in London. 62.7% of emails received a response within 1 working day. 55.2% of responses provided specialist paediatric advice to support the GP to continue managing the patient in primary care. 31% advised the GP to refer the patient to paediatric outpatients, while 7.1% were deemed to divert a potentially 'unnecessary referral' (Figure 1 ). 81.8% of community health professionals agreed that the email advice line has reduced their frequency of hospital referrals. 100% agreed that they were satisfied with the responses received. Benefits of increasing knowledge in paediatric problems were also highlighted. Six paediatric registrars felt that managing the responsibility of answering the emails alongside their clinical duties was feasible. 5/6 surveyed registrars also felt the advice line enhanced their own knowledge and learning. Conclusion: The email advice line supports the management of paediatric patients in the community and potentially reduces referrals. It enables services to be signposted and directs referrals more effectively, so that patients see the 'right person, right place, first time.' GPs valued the ease of access and efficiency of response for specialist advice, and patient satisfaction was reported by GPs as high. We believe this service empowers and enables GPs to manage paediatric patients with more confidence, and offers a unique opportunity to enhance education.